P2X7 Receptor Activation Induces Reactive Oxygen Species Formation and Cell Death in Murine EOC13 Microglia - Rachael Bartlett; Justin J. Yerbury; Ronald Sluyter (Mediators of Inflammation)
The P2X7 purinergic receptor is a ligand-gated cation channel expressed on leukocytes including microglia. This study aimed to determine if P2X7 activation induces the uptake of organic cations, reactive oxygen species (ROS) formation, and death in the murine microglial EOC13 cell line. Using the murine macrophage J774 cell line as a positive control, RT-PCR, immunoblotting, and immunolabelling established the presence of P2X7 in EOC13 cells. A cytofluorometric assay demonstrated that the P2X7 agonists adenosine-5′-triphosphate (ATP) and 2′(3′)-O-(4-benzoylbenzoyl) ATP induced ethidium+ or YO-PRO-12+ uptake into both cell lines. ATP induced ethidium+ uptake into EOC13 cells in a concentration-dependent manner, with an EC50 of ~130 μM. The P2X7 antagonists Brilliant Blue G, A438079, AZ10606120, and AZ11645373 inhibited ATP-induced cation uptake into EOC13 cells by 75–100%. A cytofluorometric assay demonstrated that P2X7 activation induced ROS formation in EOC13 cells, via a mechanism independent of Ca2+ influx and K+ efflux. Cytofluorometric measurements of Annexin-V binding and 7AAD uptake demonstrated that P2X7 activation induced EOC13 cell death. The ROS scavenger N-acetyl-L-cysteine impaired both P2X7-induced EOC13 ROS formation and cell death, suggesting that ROS mediate P2X7-induced EOC13 death. In conclusion, P2X7 activation induces the uptake of organic cations, ROS formation, and death in EOC13 microglia.